2020
DOI: 10.1098/rsos.191638
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for localization and urbanization economies in urban scaling

Abstract: We study the scaling of (i) numbers of workers and aggregate incomes by occupational categories against city size, and (ii) total incomes against numbers of workers in different occupations, across the functional metropolitan areas of Australia and the US. The number of workers and aggregate incomes in specific high income knowledge economy related occupations and industries show increasing returns to scale by city size, showing that localization economies within particular industries account for superlinear e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…But another interpretation is that measures like population size (or industrial diversity) alone do not take into account the specific combinations of people and technology in a city that can increase (or decrease) the potential for capability recombination. This is consistent with the findings by Balland & Rigby [19], for example, who found that high-complexity patenting tends to be geographically concentrated, yet not exclusively in the most populous cities; or by Sarkar et al [104], who found that to understand urban economic performance the specific intra-city composition of economic and social activity and physical infrastructure should be taken into account, in addition to just population size. This suggests that our estimate of city collective know-how may capture such intra-city composition.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 90%
“…But another interpretation is that measures like population size (or industrial diversity) alone do not take into account the specific combinations of people and technology in a city that can increase (or decrease) the potential for capability recombination. This is consistent with the findings by Balland & Rigby [19], for example, who found that high-complexity patenting tends to be geographically concentrated, yet not exclusively in the most populous cities; or by Sarkar et al [104], who found that to understand urban economic performance the specific intra-city composition of economic and social activity and physical infrastructure should be taken into account, in addition to just population size. This suggests that our estimate of city collective know-how may capture such intra-city composition.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 90%
“…According to this proposition, in the long term, the general performance of a particular city would be largely independent of individual political choices. However, the universality proposition has been challenged, either by counter-evidence [10,28,[35][36][37], or by methodological arguments [38][39][40][41][42]. Thus, the universality proposition is still an open question both from the methodological and the theoretical point of views.…”
Section: Introductionmentioning
confidence: 99%
“…After all, the total employment patterns could be quite dispersed, with a major portion of jobs scattered throughout the metropolitan areas rather than being concentrated in the centres. However, the PECs are still dominant as they attract, relatively, the highest proportion of workers-especially in knowledge-based and skillsbased professional occupational categories that generate the highest incomes (Sarkar et al, 2020).…”
Section: Tracking the Connectivity Index Against Seifa Decilesmentioning
confidence: 99%